2014
DOI: 10.1155/2014/184237
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Histiocytosis of the Thyroid with Multiple Cervical Lymph Node Involvement Accompanying Metastatic Thyroid Papillary Carcinoma

Abstract: A 37-year-old male case was admitted with goiter. Ultrasonography of thyroid showed a 5 cm cystic nodule in the left lobe with a 1.5 cm solid component. Fine needle aspiration biopsy revealed atypia of undetermined significance or follicular lesion. The patient was operated on. The pathological diagnosis was reported as papillary thyroid carcinoma. The immunohistochemical examination showed multiple foci of Langerhans cell histiocytosis involving both lobes. The patient died due to cardiac arrest with respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…In a study by Sieni et al the median age of patient was 8.7 years with 16 males and 11 females. 1 The incidence of the disease is ten times less in adults with a mean in the thirties and only 10 percent above 55 years of age are affected by the disease. 5 In this study 29.2% were adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Sieni et al the median age of patient was 8.7 years with 16 males and 11 females. 1 The incidence of the disease is ten times less in adults with a mean in the thirties and only 10 percent above 55 years of age are affected by the disease. 5 In this study 29.2% were adults.…”
Section: Discussionmentioning
confidence: 99%
“…1 The disease can occur at any age, but a peak is seen at 5-10 years. The etiology remains to be elucidated with unknown pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It could involve several organs and systems such as the skin, lung, bone, liver, lymph nodes, hypothalamus, and central nervous system. [ 1 3 ] The exact etiology is still under investigation. [ 4 , 5 ] Differentiated thyroid cancer, especially papillary thyroid carcinoma (PTC), is the most common subtype of thyroid cancer, having an increasing incidence worldwide, possibly due to the increasing use of diagnostic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, reports of such case are very few. [ 3 , 6 , 7 ] This paper aimed to report such a rare case and discuss its clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…Over the next LCH in addition to PTC, which was confirmed by immunohistochemistry. 5 Ceyran et al 6 reported a similar case in a 37-year-old man who presented with a thyroid swelling and lymphadenopathy. He was confirmed on histopathology to have both these entities along with lymph node metastasis.…”
Section: A S E Rep Ortmentioning
confidence: 91%